Bank-specific determinants of explicit deposit insurance adoption: A global analysis - Mohammad, Khalil Ullah; Adnan, Noor Ul Haya; Kasheer, Muhammad; Ali, Madeeha (Universitas Islam Indonesia, 2025)
Purpose — The adoption of explicit deposit insurance has increased significantly over the past two decades, yet there is limited evidence on how bank-specific factors influence this decision. This study addresses this gap by investigating the determinants of explicit deposit insurance adoption.Method — This study uses 25 years of unbalanced data from 107 countries and a probit model to identify the key factors influencing the adoption of the financial safety net. Findings — The analysis reveals that bank-specific factors significantly influence the decision to implement explicit deposit insurance. However, bank capitalization does not significantly impact the decision. Additionally, regulatory quality, economic growth, and financial crises are critical determinants of the adoption decision. The likelihood of adopting explicit deposit insurance also varies considerably across different income groups in countries. Implications — The study provides valuable insights for policymakers on the factors to consider when implementing this financial safety net.Originality — This study contributes to the existing literature by highlighting the previously overlooked role of bank-specific factors in adopting explicit deposit insurance.